Liminal identities: youth migration and narratives of belonging - Zlatic, Franka (2024)
This thesis captures the outcome of two crucial thresholds in young migrants’ lives: moving to the UK and coming of age. It was inspired by personal experience but born out of a need to academically reflect on the growing number of young people who choose to grow up abroad and select the UK as either their temporary or permanent home. The study included both EU and non-EU migrants who moved in a highly transnational context, characterised by flexibility, uncertainty, individuality and openness to the new. It draws on qualitative research conducted online with 27 migrants who came to the UK from a total of 24 countries of origin. Some of them came to the UK to pursue their academic degrees, and some came straight after finishing their degree in their home country. In that sense, migrants of this research have been defined as young, highly skilled and highly mobile. This thesis aimed to contribute to the growing literature on migrant belonging, and more specifically to offer a perspective on the way young migrants create attachments. It does so by combining and operationalising several theoretical concepts that were broadly described under a transnational framework: social anchoring, embedding and liminality. The research questions reflected areas that contribute towards establishing the feeling of (non)belonging; namely identity, the symbolic and geographical attachment to space, and ultimately, relationships and connections migrants engage with. This study makes several contributions. (1) It advances the use of the theoretical concepts of social anchoring and embedding in migration research by unravelling - through the analytical lens of liminality – migrants' weak ways of belonging and shallow embedding. (2) It bridges scholarship on individualised practices that characterise youth migration with the relational nature of the concept of belonging, by showing that belonging is individualistically felt, but relationally conditioned. (3) Building on the previous point, it explores the possibility of non- belonging which has so far been neglected in researching migrants’ connections post- move. (4) Finally, it emphasises the temporal factor in shaping feelings of belonging, connected to age at migration and the life-course. (5) Methodologically, it presents a novel way to visually capture the simultaneity of transnational (non)belonging, by inserting counter-mapping as one of the prompts within the qualitative research design. Ultimately, this thesis argues that belonging for young and highly skilled migrants results in an in-between state and suggests that belonging more often than not remains merely a yearning.